Variable Structure Control of Two-Wheels Inverted Pendulum Mobile Robot - Nawawi, S.W; Ahmad, M. N.; Osman, Johari H. S. (School of Postgraduate Studies, UTM, 2006)
In this paper the position and posture control for the wheeled inverse pendulum type mobile robot is discuss base on simulation result of two type of controller. The robot in this consideration has two independent driving wheels in same axis, and the gyro type sensor to know the inclination angular velocity of the body and rotary encoders to know wheels rotation. this paper will discuss the control algorithm to make the robot autonomously navigate in two dimensional plane while keeping balance its pole.